P04 Adiposity of Healthy, Full-Term Breast-Fed and Formula-Fed Infants: A Prospective Cohort Study. (4th June 2013) - Gale, C; Jeffries, S; Logan, KM; Parkinson, JRC; Uthaya, S; Durighel, G; Thomas, EL; Bell, J; Modi, N
Abstract : Aims: Although an association exists between method of feeding in infancy and increased risk of later overweight and obesity, it is unclear whether this represents a causal relationship. One plausible mechanism of action is through alteration in adiposity in infancy. We aimed to compare longitudinal changes in adiposity in healthy, full-term, breast-fed (BF) and formula-fed infants (FF). Methods: Research Ethics Committee and NHS approvals were obtained. With informed maternal consent, healthy, term infants underwent whole body magnetic resonance imaging and hepatic spectroscopy to assess body composition and intrahepatocellular lipid (IHCL) content. Investigations were performed in natural sleep on two occasions, shortly after birth (T1), and between two and three months (T2) in accordance with our previously published protocols. Anthropometric measurements were obtained at both visits. Feeding was categorised according to World Health Organisation definitions. Comparison was made between exclusively or predominantly BF, and exclusively or predominantly FF infants. We used independent sample t-tests to compare body weights and multivariable regression to examine total and regional adipose tissue volumes at T2, with adjustment for baseline adiposity and body weight. Adipose tissue volumes (litres) and IHCL (ratio of lipid to water peak) are presented as mean (95% confidence interval). Results: Eighty-six infants were studied at T1, median [interquartile range] 13 [8–19] days, and 73 at T2, 63 [57–70] days. Of these, 38 infants were wholly or predominantly BF and 26 wholly or predominantly FF at both time points. At T2, while FF infants were heavier (mean, standard deviation: 5.399kg, 0.661kg; FF 5.435kg, 0.68kg); p = 0.045), total adiposity was not significantly different (BF 1.516 (1.433, 1.600); FF 1.633 (1.531, 1.735); p = 0.08). There were no statistically significant differences in regional adipose tissue volumes or IHCL (BF 2.398 (1.838, 2.958); FF 2.406 (1.708, 3.103); p = 0.9). Conclusions: While adiposity does not differ substantially between BF and FF infants by 9 weeks of age, further longitudinal evaluation is required to determine if the trend to greater total adiposity in FF infants is subsequently amplified.